Bioactive compounds from sterm bark of Entada Spiralis RIDL - Harun, Aiza; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian; Wan Mat Khalir, Wan Khaima Azira (Penerbit USM, 2010)
Introduction: Entada spiralis Ridl. (Leguminoceae) which is locally known as beluru or sintok is a liana or woody climber that grows wildly in Malaysia. The isolation and characterisation of the major chemical constituents from the bioactive extract of the stem bark of E. spiralis has been carried out. Our previous study revealed that the methanol extract was active against dermatophytes that causes skin infections. Strains of dermatophytes, Trichophyton mentagrophytes ATCC 9533, Trichophyton tonsurans ATCC 28942 and Microsporum gypseum ATCC 24102 were used.